University students perception of covid-19: A metaphor analysis - EMİNOĞLU KÜÇÜKTEPE, SEVAL (My University, 2020)
The purpose of this research is to reveal how university students perceive COVID-19 metaphorically during the pandemic process. The research was carried out with the state university students of the faculty of education in the Marmara region in the 2019-2020 academic year. In order to gather data for the research, an open-ended questionnaire was prepared to find out the views of the university students participating in the study about COVID-19. The students were asked what is comparably associated with Covid-19 in regard to their views. Students were asked to complete the sentences like “COVID-19 is like a …… Because ……..”. This research is a phenomenological design study and it is one of the qualitative research methods. While analyzing the data, a data analysis method consisting of five steps was followed: coding and sorting, sample metaphor image compilation stage, category development stage, ensuring validity and reliability stage, and transferring metaphors with quantitative data. The obtained data was first grouped in line with the common features of the metaphors and categories were created. As a result of the research, the produced metaphors by university students gathered into ten groups as "freedom restriction", "spreading/contacting", "cause of death", "uncertainty", "enlightening-stimulating", "infectious and adhesive type", "enemy", "dangerous creature", "dirt-stain" and "COVID-19 being as an exam/test".
Keywords: COVID-19; university student; metaphor